2019
DOI: 10.3390/app9081527
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Achievable Data Rates of Broadband Power Line Communication for Smart Metering

Abstract: Building real Smart Metering and Smart Grid networks is very expensive and time-consuming and also it is impossible to install different technologies in the same environment only for comparison. Therefore, simulation and experimental pilot measurements are an easy, economical, and time-affordable solution for a first comparison and evaluation of different technologies and solutions. The local area networks (LAN) are the core of Smart Metering and Smart Grid networks. The two predominant technologies are mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…This article describes the simulations shallowly and summarizes the basic possibilities of PLC simulation in NS-3. An article close to this work is [ 56 ], where an advanced G.hn simulation was provided in the frequency band 1.8–30 MHz. The work examines BPLC topology in NS-3 where the channel capacity, depending on the branch length and the impedance, is simulated.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…This article describes the simulations shallowly and summarizes the basic possibilities of PLC simulation in NS-3. An article close to this work is [ 56 ], where an advanced G.hn simulation was provided in the frequency band 1.8–30 MHz. The work examines BPLC topology in NS-3 where the channel capacity, depending on the branch length and the impedance, is simulated.…”
Section: State Of the Artmentioning
confidence: 99%
“…Ref. [ 56 ], described above, is also related to this section. Advanced BPLC simulation of the G.hn standard was performed with topology, which was created on the basis of a real BPLC network.…”
Section: State Of the Artmentioning
confidence: 99%
“…On the other hand, in BPL networks on the LV, longer distances without repeaters are typical [22], but in MV topologies the positions of repeaters are fixed. Those repeaters are deployed in every distribution substation, and it is also necessary to implement repeaters on both sides of a transformer due to its physical disconnection and galvanic isolation of the powerline [23,24].…”
Section: Bpl On Medium Voltage (Mv)mentioning
confidence: 99%
“…Based on the literature review covered in this section, we found that there are no pertinent articles presenting differences between common methods of powerline communication simulations and real results of devices deployed on power lines under the load. With our experiences, with performance evaluation of networks based on PLC and mutual cooperation with electric utilities in the Czech Republic [22,[63][64][65][66][67], we mainly focus on correlating simulations and real measurements with consequent outcomes. Our goal is to enhance knowledge in terms of determining the necessity of repeater usage in PLC network design.…”
Section: Real Measurements-related Workmentioning
confidence: 99%
“…Attackers can decrease the network bandwidth or obtain the traffic including private data such as search histories, login information, and device usage patterns by exploiting the vulnerabilities in firmware upgrades to install malicious firmware [ 9 ]. Mlynek et al [ 10 ] show the data rates of different power line communication protocols used in smart metering, but it concludes that all PLC will suffer from nodes being not close enough to their peers (i.e., the attenuation of the power line is proportional to the length of the power line) as well as from the power quality of the grid. The proposed solution of having repeaters at certain distances is not feasible in our case, as we aim to not add any new equipment on the grid and to only use what has already been deployed in the field.…”
Section: Contextmentioning
confidence: 99%